The Sewol Ferry Disaster: Experiences of a Community-Based Hospital in Ansan City. (29th September 2016) - Park, Jong-Hak; Cho, Hanjin; Kim, Joo Yeong; Song, Joo-Hyun; Moon, Sungwoo; Cha, Sang Hoon; Choi, Byung-Min; Han, Chang-Su; Ko, Young-Hoon; Lee, Hongjae
Abstract: The Sewol ferry disaster is one of the most tragic events in Korea's modern history. Among the 476 people on board, which included Danwon High School students (324) and teachers (14), 304 passengers died in the disaster (295 recovered corpses and 9 missing) and 172 survived. Of the rescued survivors, 72 were attending Danwon High School, located in Ansan City, and residing in a residence nearby. Because the students were young, emotionally susceptible adolescents, both the government and the parents requested the students be grouped together at a single hospital capable of appropriate psychiatric care. Korea University Ansan Hospital was the logical choice, as the only third-tier university-grade hospital with the necessary faculty and facilities within the residential area of the families of the students. We report the experiences and the lessons learned from the processes of preparing for and managing the surviving young students as a community-based hospital. ( Disaster Med Public Health Preparedness . 2017;11:389–393)